Achieving Hospital Efficiency through Inventory Management Strategies: A Systematic Review - Sulistioningsih, Emi; Satibi, Satibi; Yuniarti, Endang (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: In developing countries, pharmaceutical expenditures account for approximately 40–50% of total hospital costs. Therefore, effective management of medicines and pharmaceutical supplies is essential, as it significantly influences hospital operational efficiency and the quality of healthcare services.Objectives: This study aims to evaluate the impact of Economic Order Quantity (EOQ), Reorder Point (ROP), and Minimum-Maximum Stock Level (MMSL) inventory management methods on hospital efficiency.Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were applied to operate this systematic review. The articles published between 2009 and 2024 were identified through searches of Scopus, PubMed, Google Scholar, and the Garuda database. Studies that reported the application of EOQ, ROP, or MMSL methods in hospital pharmaceutical inventory management were included. A total of nine eligible studies were reviewed and synthesized to evaluate their impact on inventory efficiency indicators.Results: Nine studies met the inclusion criteria. Four studies applied EOQ and ROP methods, while five studies implemented the MMSL methods. The efficiency indicators evaluated inventory value, dead stock, stock out, inventory turnover ratio (ITOR), and customer service level. EOQ and ROP methods were associated with reductions in inventory value and stockouts, as well as improvements in ITOR and customer service levels. The MMSL generally reduced inventory value, stockout frequency, stockout value, and dead stock, either significantly or non-significantly, and increased ITOR. However, one study reported an increase in inventory value due to unstable supply conditions before implementation, and another reported a decrease in ITOR related to ordering policy constraints. Overall, the findings suggest that the EOQ, ROP, and MMSL methods generally improve inventory efficiency; however, several studies reported inconsistent or non-significant effects on certain indicators, such as the inventory turnover ratio and inventory value, under specific operational conditions.Conclusion: This systematic review indicates that the Minimum–Maximum Stock Level and Economic Order Quantity, Reorder Point methods are potentially beneficial strategies for enhancing inventory efficiency in hospital settings.